Claude Syndrome in Childhood Associated with Probable Neuro-Behcet Disease - Yavuz, Pinar; Solmaz, Ismail; Kaya, Ummusen Akca; Akgoz, Ayca; Oguz, Kader K.; Aytac, Selin; Ozen, Seza; Yalnizoglu, Dilek (Neuropediatrics, 2022)
Claude syndrome is a rare midbrain stroke syndrome characterized by ipsilateral third cranial nerve palsy and contralateral hemiataxia. So far, only a few cases have been reported in childhood. We present two children with Claude syndrome at 9 and 15 years of age. The typical clinical picture was consistent with brain magnetic resonance imaging findings. A thorough investigation regarding the underlying etiology revealed no definite diagnosis but clues suggestive of probable neuro-Behcet disease. Awareness of pediatric neurologists on arterial ischemic stroke has been increasing over the past decades, enabling timely diagnosis and appropriate management of rare childhood cases with midbrain stroke.
Keywords: Claude syndrome; oculomotor nerve palsy; hemiataxia; posterior stroke; neuro-Behcet disease